IN SEARCH FOR A DEMOCRATIC CONSTITUTION: INDONESIAN CONSTITUTIONAL REFORM 1999 - 2002 - Indrayana, Denny (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
In 1999, the Indonesian People’s Consultative Assembly enacted the First Amendment to the 1945 Constitution. Over each of the next three years, it passed a further amendment. This paper argues that the amendments lacked what have widely been accepted as key features of a democratic constitution-making process. Many of the problems related to fundamental issues within the Constitution itself. It contained two aspects seen as crucial to the identity and survival of the country by most nationalists: the rejection of an Islamic state and the imposition in its place of a nationalist state ideology, the Pancasila. This paper proposes that to resolve the difficult relationship between Islam and the state - for the immediate future at least - the preamble and Article 29 should be made as a non-amendable and ‘entrenched’. From Indonesia’s experience, beside observing the general characteristics of constitution-making process in transition, scholars should note how the symbolic value of the 1945 Constitution strongly overshadowed the way the constitutional reform took place.Keywords: Constitution, Democracy, Amendment, Reform, Indonesia.